2017
DOI: 10.1021/acs.jpclett.7b00008
|View full text |Cite
|
Sign up to set email alerts
|

Ferroelectric Alignment of Organic Cations Inhibits Nonradiative Electron–Hole Recombination in Hybrid Perovskites: Ab Initio Nonadiabatic Molecular Dynamics

Abstract: Hybrid organic-inorganic perovskites show impressive potential for photovoltaic applications and currently give rise to one of the most vibrant research areas in the field. Until recently, the electrostatic interactions between their organic and inorganic components were considered mostly for stabilization of the fragile perovskite structure. We study the effect of local interactions of polar C-N bonds in the organic layer on the nonradiative electron-hole recombination in the recently reported room-temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
80
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(81 citation statements)
references
References 77 publications
1
80
0
Order By: Relevance
“…Jankowska and Prezhdo [ 224 ] investigated the electron–hole recombination for the ferroelectric layered perovskite, (benzylammonium) 2 PbCl 4 , by combination of NAMD and time‐domain DFT (TD‐DFT). They found that the ferroelectric phase exhibited slower electron–hole recombination than the paraelectric phase due to the suppression coupling of the electronic subsystem to the high frequency phonons.…”
Section: Distribution and Rotation Of Organic Cationsmentioning
confidence: 99%
“…Jankowska and Prezhdo [ 224 ] investigated the electron–hole recombination for the ferroelectric layered perovskite, (benzylammonium) 2 PbCl 4 , by combination of NAMD and time‐domain DFT (TD‐DFT). They found that the ferroelectric phase exhibited slower electron–hole recombination than the paraelectric phase due to the suppression coupling of the electronic subsystem to the high frequency phonons.…”
Section: Distribution and Rotation Of Organic Cationsmentioning
confidence: 99%
“…At the same time, it may be worth noticing, that for another system belonging to the HOIP family, characterized with more spatially extended aromatic cation, the room-temperature stable ferroelectric phase has been experimentally confirmed [152] . Recently also the effects of local ferroelectric order on photo-generated charge recombination has been investigated by means of non-adiabatic molecular dynamics simulations for this system [153] .…”
Section: Anomalous Photocurrent-voltage Hysteresismentioning
confidence: 99%
“…Unlike the fully inorganic semiconductors used in conventional quantum well modulators, hybrid perovskites and their layered derivatives can accommodate dipolar cations. The role of the A cations in bulk perovskites has attracted attention: numerous studies have focused on optimizing mixtures of several cations for improving device performance 19 21 , investigating the possibility of alignment of dipolar cations 22 26 , and probing the rotational dynamics of dipolar cations 27 32 . Although research into low-dimensional perovskites is growing, the corresponding studies have yet to be conducted in these materials; the differences with the bulk suggest that the smaller cations in low-dimensional perovskites may add intriguing properties.…”
Section: Introductionmentioning
confidence: 99%